Social Change and Mutations in the Human Sciences Applied to Physical and Sporting Activities in Tunisia - Nasri, Bechir; Souid, Ines (Advances in Social Sciences Research Journal, 2024)
This research focuses on the relationship that exists between scientific transformations in human sciences applied to physical and sporting activities during social change in Tunisia after the revolution. The main objective of our study is to identify the link between studies published in the sociology of sport in relation to the major social changes in Tunisia after the revolution. The data was collected through the analysis of research and studies published by teacher-researchers in sociology of sport at the higher institutes of sport and physical education of Tunisia in various international journals. The main results of this article show that the research carried out during this period is not directly linked to the changes that have arisen from the world of Tunisian physical education, but it aims to position it according to Western sporting social phenomena. In addition, the existence of certain studies which take into account the training process and the conceptions of learning physical education in contemporary Tunisian schools.